Vikingetidens gravskik i Danmark – Spor af begravelsesritualer i jordfæstegrave - Ulriksen, Jens (Kuml, 2011)
Viking Age burial practices in Denmark Traces of burial rituals in inhumation graves The hypothesis examined in this article is that the broad impression of grave forms and burial traditions gained from a comparison of contemporaneous inhumation cemeteries of the Viking Age also includes coincidences in the actions and rituals that can be deduced from the remains present in the graves. A mapping of the traces left by these actions is based on evidence from a number of Viking Age cemeteries in present-day Denmark, Scania and Southern Schleswig, excavated between 1895 and 2007. The resulting record reveals some regional differences but also includes some clear traits that are found repeated at numerous cemetery sites. In the present context, attention is focussed on a number of elements seen in the graves which are then presented, exemplified and discussed. In an attempt to interpret these traces, use is made of Nordic mythology, written sources from the Viking Age and Middle Ages and comparative religious studies relating to the mentality and cosmology of the Viking Age. As a starting point, two recently excavated cemeteries on Zealand are presented, namely Kirke Hyllinge Kirkebakke and Trekroner-Grydehøj near Roskilde (fig. 1). Both contain significant information with respect to burial rituals in the Viking Age. Kirke Hyllinge Kirkebakke Kirke Hyllinge Church stands on the highest point in the area, c. 43 m above sea level (fig. 2). The cemetery here had at its core an older barrow and from here the graves extended out over an area measuring 80 m E-W and about 35 m N-S (fig. 3). In all, 28 burials were investigated, of which two were double graves, one contained the remains of three people and yet another the remains of four individuals. Further to these were three presumed inhumation graves and a cremation burial. About 80% of the graves were oriented N-W or NW-SE. Analysis of the human bones revealed that these represented the remains of two males, two females and 13 individuals of indeterminable gender. Of the skeletal remains for which it was possible to determine age, two were of children between the ages of seven and ten, three individuals were less than 20 years old, ten were between 20 and 35 and one person was 35-45 years old (fig. 4). There were artefacts in 17 of the graves and it became apparent that the equipment had been placed in two different locations in the grave (fig. 5). Accompanying the deceased on the floor of the grave lay artefacts such as knife, distaff whorl, whetstone, belt buckle or glass beads. Similar artefacts could also be found distributed through the grave fill above the deceased, often in a more or less damaged state. A particular phenomenon which emerged was the presence of skeletal parts that had been placed in the grave fill. An example of this is grave A590, which was 70 cm deep. On the base of this grave lay the remains of a woman with her equipment. Distributed through the fill above her were teeth from two different adult individuals and three further molars from a c. 8-year-old child. There was also burnt human bone. Another example is grave A569 which, in addition to the deceased at the base of the grave, contained parts of an adult and a c. 10-year-old child. Small pieces of burnt bone were found in 16 of the 31 definite or presumed inhumation graves. The quantity of bone varied from just a few grams to more than 200. Burnt human bone only occurred in two inhumation graves, A590 and A594, and in cremation grave A629. Stones of varying size were found in the fill or at the base of eight graves. The quantity – in terms of both number and weight – varied greatly. Most striking was their presence in A590 and A608. In a couple of cases the stones showed the effects of fire. The distribution of graves across the excavated area showed a tendency towards clustering but no systematic pattern emerged with regard to gender or grave orientation within these groups. Immediately to the south of inhumation grave A583 there were two identical constructions, each comprised of four posts (fig. 6). The two four-poster constructions are so similar, and are situated in such a way, that it seems very likely that one replaced the other. Four-poster constructions can represent a light building, a tent or a frame in, or on, which the deceased was placed for a shorter or longer period prior to actual burial. Trekroner-Grydehøj, Roskilde Grydehøj is a small hill on the eastern periphery of Roskilde. At the beginning of the Viking Age, the west-facing slope of the hill in particular was used as a burial ground (fig. 7). The cemetery had as its core a cluster of earlier burial monuments from the Neolithic and Early Bronze Age located on the top of the hill (fig. 8). Of the 27 inhumation graves detected, 25 lay within an area measuring c. 50 x 33 m running down the west-facing hillside. Most of the graves, c. 80%, were oriented N-S or NW-SE. In addition to single graves there were also double graves in which one body had been placed on top of the other. However, there was also an example where they lay in continuation of one another (fig. 9). Three inhumation graves, of which one was a double grave, had burnt human bone in the grave fill (fig. 10). The results of the analyses of human bone are shown in figures 11 and 12. There were artefacts in 21 graves; these were partly associated with the deceased on the base of the grave and partly found distributed through the overlying fill. A505 differed from the other graves. At the top there were many fieldstones and flint nodules and along its eastern side were three large boulders. The upper part of the grave was found to contain most of the skeleton of a female and parts of a skeleton of a male (fig. 13). At the base of the grave was the skeleton of a female (fig. 14). By her right thigh was an iron point fitted into a solid cast bronze socket which originally had a wooden shaft (fig. 15). This presumably represents a ceremonial object, perhaps a symbol of Odin, master of sorcery. In other words, the artefact could be a völva’s staff. At the foot of the grave, a menhir had been erected over the rear half of a medium-sized dog which had been severed in the middle (fig. 16). Along the eastern side of the grave lay the remains of an old stallion; these partially covered the woman’s left side from the waist downwards. Stones were found in eight graves: in the fill, at the base of the grave or over the skeleton (fig. 18). The most striking of these were the large boulders and the many smaller stones seen in the fill of grave A505. A total of 18 of the 27 inhumation graves were found to contain burnt bone fragments; in the great majority of cases these could not be identified to species. It was, however, possible to establish that there were burnt human remains in graves A2036, A2047 and A2059. The distribution of the graves showed a weak tendency towards grouping. There was no systematic pattern with respect to gender or grave orientation within these groups (see fig. 8). There was a four-poster construction by grave group C and inhumation graves A2030 and A2079, but it is unclear to what degree this was associated with the Viking Age cemetery. Traces of rituals in the Viking Age inhumation graves The grave pit The orientation of the grave pit relative to the points of the compass shows some regional differences. In Northern Zealand and Scania graves orientated N-S are dominant, whereas in Southern and Western Zealand they are more mixed with E-W oriented graves (figs. 20 and 21). The tendency to orientate graves in an E-W direction is more pronounced on Funen (fig. 22), and in Jutland E-W orientated burials are clearly dominant. The orientation of the grave pit appears not to be founded on very fixed perceptions of a religious character. It seems rather to be an expression of local or regional tradition. Coffins Extensive use was made of the ‘available box’ principle when a coffin was needed for a burial. In general, there appears not to have been any immediate status-related link between coffin form and grave content with respect to simple coffins. Double graves, secondary burials and bone depositions Most of the graves in which there was a secondary burial above a primary interment reveal clear evidence of the care taken to ensure that the new grave lay within the limits of the original grave pit. We can only speculate as to the background for the double and secondary burials. There could have been a ritual killing, but this is unlikely to have been the case in all instances. The reason for human body parts having been included as grave goods could be an expression of ancestor worship; the graves of particularly important people within or outside the family could have been dug up and the bones and artefacts removed in order for them subsequently to be included in the graves of other deceased members of the family. Burnt bone in the grave fill Small pieces of white calcined bone are a familiar phenomenon in Viking Age inhumation graves. It seems obvious that the burnt bone represents a ritual. The bones have been crushed before being scattered into the grave as it was back-filled. In fortunate cases the bone can be identified to species and both humans and animals are represented. The unburnt corpse at the base of the grave should be considered as the actual primary occupant of grave, whereas the cremated bone constitutes part of the burial fittings. In ‘Odin’s Law’, which is reproduced in the Ynglinga Saga, cremation is prescribed, but inhumation burial increased in dominance during the course of the Late Germanic Iron Age and Viking Age. The burnt bone in the inhumation graves could, however, be a relic of an older tradition and use – a tribute to Odin. Unburnt animal bone The unburnt animal bones in the inhumation graves represent a broad spectrum of domestic animals such as pigs, cattle, poultry and sheep/goats. It seems obvious to perceive these bones as representing offerings of food, but the animals could have had further symbolic meaning than food alone. The pig has a role in Nordic mythology, including in the form of the hog Gyldenbørste, Frey’s attribute. Similarly, a hog is sacrificed to Frey. Cattle also had a role as offering in the sacrifice (blot), which is reflected in the term blótnaut, i.e. cattle intended for blot. Dogs do not occupy a prominent role in Nordic mythology but occur commonly in Viking Age graves, both in a cremated and an unburnt state. It is possible that the dog performed the role of spiritual guardian on the journey to the Kingdom of the Dead, or that it symbolised the transition from life to death. The horse encompasses symbolic elements which it is important to note. Sleipner was Odin’s eight-legged horse, and it carried him to and from the Underworld. The horse is, accordingly, perceived as an important auxiliary spirit for those skilled in sorcery in their contacts with the afterlife. The horse was also an important animal in the blot and formed part of ritual meals in connection with this. The presence of animals in the graves is equivocal. There is an explanation which immediately springs to the mind of a modern person but the significance can be accentuated and expanded both mythologically and ritually. It seems clear that there is an embedded symbolism in at least some of the animals placed in the graves and in the treatment of these animals prior to burial. An example of a grave containing several animal offerings is A505 at Trekroner-Grydehøj (see figs. 13, 14 and 16). Stones in the grave pit The purpose of covering or filling graves with stone packings and the placing of boulders of various sizes in the fill, on the base of the grave or directly on the corpse, does not appear immediately evident on the basis of the archaeological evidence. There are descriptions from the saga literature in which burials and stones belong together, for example in Gisli Sursson’s Saga. It seems obvious that the stones are intended to prevent the corpse returning from the dead. In grave A505 at Trekroner-Grydehøj a small square ‘menhir’ had been set on edge on top of the dog’s corpse (see fig. 16). Similarly, a stone was placed on top of the animal bones at the foot of grave A590 at Kirke Hyllinge Kirkebakke. On the face of it, the menhir on the floor of the grave makes most sense if the grave had stood open, or was only partially back-filled, for a period during which the stone was, as a consequence, fully visible. Artefacts in the grave fill The deposition of artefacts, whether intact, damaged or unfinished, in the grave fill, reflects burial rituals in which the actual back-filling process was important. The significance of the damaged artefacts is not immediately clear. A situation worthy of note is that, in several instances, damaged distaff whorls and brooches, i.e. female-related artefacts, are found in graves where the deceased interred on the base of the grave was a man. It seems entirely possible that the destruction of feminine artefacts and their deposition high up in the grave fill should be seen in a gender-related context. Spinning and weaving were very strongly linked to the female sphere and the tools associated with these activities can be perceived as a metaphor for performance of magic. Accordingly, the fact that the artefacts are damaged could have been linked with the perception of magic as being strongly effeminate and, in reality, a taboo for men. Conclusion An interesting aspect of Viking Age burial practices is that it can be shown that rituals and ceremonies took place over longer periods – days, weeks, months and years. This is apparent partly from the presence of artefacts, evenly distributed burnt bone fragments and remains of animals and humans in the grave fill, and partly from the traces of the careful re-opening of a grave in order to inter a further corpse precisely within the limits of the original grave pit. Another thought-provoking aspect relates to the human and animal body parts, both burnt and unburnt, which were added to the grave fill during the back-filling process. It is obvious that there must have been a well-defined difference between whether bones were cremated or unburnt. Another practice, for which the background does not seem immediately clear, is that stones in various amounts and of various sizes were added to some graves. It must be presumed that the purpose of a packing of fist- to head-sized stones differed from that of a heavy boulder placed directly on the body. Stones erected on the base of a grave did not arrive there by chance. They apparently occur particularly at the head and feet of the deceased and, in some instances, in association with animal bones. Artefacts do not occur exclusively on the base of the grave together with the deceased, but can also be present up in the grave fill. Often the artefacts are fragmented and all the evidence suggests that this destruction took place intentionally prior to deposition. It is difficult to say anything about the powers which may have been ascribed to these everyday artefacts, and perhaps it is not the object in its usual surroundings which constitutes a problem. It could, to a greater degree, be the object in association with something unusual which constituted a potential risk. Examples include artefacts such as ornaments and distaff whorls which are associated with women and, as such, could have been more or less taboo for men. Despite these variations, the perception of behaviour and customs was uniform over great distances, both in time and space. The common denominator is not always the most conspicuous aspect but can be deduced from the details which are revealed by archaeological excavations of the cemeteries of the period. What these traces as a consequence actually represent with respect to this world and the next is something, as children of the 20th century, we can only attempt to understand and argue the case for. But it could very well turn out that it all remains a question of belief. Jens Ulriksen Næstved